(untitled) (Studia Archaeologica, 2022)
This is article ancient nomadic whip. From time immemorial, nomads have used and developed a variety of equipment to suit the specifics of their use of horses for riding. One of them is a whip. The whip is traditionally made of solid wood with a strap and a tie. Archaeological excavations have shown that whip-related artifacts have been found in ancient tombs, but there have been a number of cases where whip trees have been found in rock burials, a unique form of nomadic burial. Based on these findings, a whip, a type of horse equipment, is described. According to the materials the ancient whip tree was found in 1 stone tomb from the Xiongnu period, 1 from the related rock burials in the Ancient Turkic period, 4 from the rock burials in the Great Khitan state, 3 from the Mongols period rock burials, and a total of 9 items were artifacts. Эртний нүүдэлчдийн ташууртай холбогдох олдворууд Товчлол. Нүүдэлчид нэн эрт цагаас адууг уналга эдэлгээнд хэрэглэх явцдаа хэрэглээний онцлогт тохирсон олон төрлийн тоног хэрэгслийг бүтээн бий болгож, хөгжүүлэн уламжилсаар иржээ. Тэдгээр бүрдэл хэсгийн нэг нь ташуур юм. Ташуурын ишийг ширхэг нягт модоор, сагалдарга болон зангиаг сураар хийдэг уламжлалтай. Археологийн судалгаагаар эртний чулуун дарааст булшнаас ташууртай хамааралтай олдвор олдоод байх нөхцөл тун бага ч нүүдэлчдийн өөр нэг оршуулгын өвөрмөц хэлбэр болох хадны оршуулгаас ташуурын мод илэрсэн хэд хэдэн тохиолдол байдаг. Эдгээр олдворт тулгуурлан адууны тоног хэрэгслийн нэг ташуурын талаар өгүүллээ. Түлхүүр үгс: Эртний нүүдэлчдийн ташуур, дундад зууны үед ташуурыг уран зургийн дурсгалд дүрсэлсэн нь, ташууртай холбогдох зарим зан үйл.